The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1527476420933584
|View full text |Cite
|
Sign up to set email alerts
|

Heroism as Narrative Strategy: Children’s Animation and Modernity in Chinese TV

Abstract: Entertaining animated television programs often carry significant educational and national discourses that are rarely given much scholarly attention. This article examines the Chinese children’s animation program Boonie Bears and explores its narrative strategies in portraying heroism. By employing content analyses, in-depth interviews, and focus groups, the article discusses how producers construct animation heroes according to the ideological framework of the Communist Party, economic preferences embedded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…More specifically, superheroes tend to be perceived as those who are willing to shoulder greater responsibilities to fulfill others’ needs. In a related vein, Zeng and Chan (2020) found that the narratives of heroism in Chinese culture were more likely to emphasize that heroes should sacrifice their own interests to serve collective interests. Zhouxiang and Hong (2019) also argued that top Chinese athletes have usually been regarded as national heroes and they have played an important part in the construction of nationalism and patriotism.…”
Section: Perception Of Heroes In Collectivistic Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, superheroes tend to be perceived as those who are willing to shoulder greater responsibilities to fulfill others’ needs. In a related vein, Zeng and Chan (2020) found that the narratives of heroism in Chinese culture were more likely to emphasize that heroes should sacrifice their own interests to serve collective interests. Zhouxiang and Hong (2019) also argued that top Chinese athletes have usually been regarded as national heroes and they have played an important part in the construction of nationalism and patriotism.…”
Section: Perception Of Heroes In Collectivistic Culturesmentioning
confidence: 99%
“…However, previous studies did not consider the influence of cultural differences on perceptions of different types of heroes. As mentioned previously, the narratives of heroism in Chinese culture tend to emphasize that heroes should sacrifice their own interests to serve one’s country and focus on the construction of nationalism and patriotism ( Chen et al, 2016 ; Zeng & Chan, 2020 ). The findings from Studies 1–4 demonstrated that Chinese participants were more likely to use patriotic to define a hero compared with American participants.…”
Section: Studymentioning
confidence: 99%